In-situ joule heating-triggered nanopores generation in laser-induced graphene papers for capacitive enhancement. (January 2022) - He, Meihong; Wang, Guantao; Zhu, Yuxiang; Wang, Yanan; Liu, Fu; Luo, Sida
Abstract: Laser-induced graphene (LIG) technology featuring low-cost, high-efficiency and scalability has presented great advantages in micro-supercapacitors (MSCs) fabrication. However, the limited capacitance of LIG based MSCs is still hindering their further development. Herein, we introduce joule heating as a critical in-situ treatment merged with the assembly of laser-induced graphene paper based MSCs (LIGP-MSCs) toward capacitive enhancement. By increasing heating-treatment temperature from ∼20 to 500 °C, the number of nanopores in LIGP continuously increases, attributed to the gradual decomposition of amorphous carbon components. The resulting joule-heated LIGP (J-LIGP) with improved specific surface area (160.97–533.49 m 2 /g) and pore volume (0.179–0.553 cm 3 /g) as well as superhydrophilic surface is highly suitable to be employed as J-LIGP-MSCs microelectrodes. By investigating process dependent performance, the J-LIGP-MSCs heated at 500 °C for 60 min delivers a significantly improved specific areal capacitance ( C A ) of 13.71 mF/cm 2 at 10 mV/s, which is approximately six-fold higher than that of unheated LIGP-MSCs. By further exploring and optimizing the process efficiency, J-LIGP-MSCs with a C A of 12.61 mF/cm 2 has been achieved by 550 °C heating for only 5 min. Along with superior mechanical flexibility, cyclability and structural modularity, the proposed in-situ joule heating treatment is finally proved to be a universal approach for consistently enhancing the C A of LIG based MSCs processed under various chemical modifications. Graphical abstract: A facile and general approach for enhancing the capacitance performance of laser-induced graphene paper based MSCs (LIGP-MSCs) are creatively proposed and demonstrated by an in-situ joule heating processing strategy, revealing outstanding potential for fabrication of high-performance LIG based MSCs. Image 1